Antegrade Chronic Total Occlusion Strategies: A Technical Focus for 2020 - Calum Creaney; Simon J Walsh (Interventional Cardiology: Reviews, Research, Resources)
Chronic total occlusions (CTOs) are common in patients with ischaemic heart disease. In many countries, patients with CTOs are underserved by percutaneous coronary intervention (PCI). One of the barriers to CTO PCI is the technical challenges of these procedures. Improvements in technique and dedicated devices for CTO PCI, combined with advances in procedural strategy, have resulted in a dramatic increase in procedural success and outcomes. Antegrade wiring (AW) is the preferred initial strategy in short CTOs, where the proximal cap and course of the vessel is understood. For many longer, more complex occlusions, AW has a low probability of success. Dissection and re-entry techniques allow longer CTOs and those with ambiguous anatomy to be crossed safely and efficiently, and CTO operators must also be familiar with these strategies. The CrossBoss and Stingray system is currently the primary targeted re-entry device used during antegrade dissection and re-entry (ADR), and there continues to be an evolution in its use to increase procedural efficiency. In contrast to older ADR techniques, targeted re-entry allows preservation of important side-branches, and there is no difference in outcomes compared to intraplaque stenting.